EFFECTS OF ARECA NUT AND ITS PRODUCTS ON BLOOD PRESSURE IN POPULATION OF NAWABSHAH SHAHEED BENAIRABAD - Altaf Khan Pathan1 , Aftab Hussain Pathan2 , Bhojo Mal Tanwan3 , Masood Nabi Noor Dahri4 , Hajira Naila Rahu5 , Mevo Khan Zardari6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
ABSTRACT INTRODUCTION: Areca nut is consumed as a chewing material by around 600 million individuals around the world. It is assessed that 10 to 20% of the world’s people use areca nut in different forms, regularly blended in betel quid OBJECTIVES: To determine the effects of areca nut and its products on Blood pressure. MATERIAL & METHODS: This case control study was carried out on community of Nawabshah, Shaheed Benazirabad. In this study 368 study subjects were included. Case group comprised of 184 study subjects regular users of areca nut and its products like pan, gutkha, supari and mainpuri. In other group 184 healthy controls were selected who were non users of areca nut or its products. Blood pressure of participants was measured by mercury sphygmomanometer by auscultatory method. DURATION: From Jan 2018 to Jun 2018. PLACE: Nawabshah Shaheed Benazirabad. RESULT: Total 368 subjects were selected in the study in which 226 were Males (61.42%), 142 were females (38.58%). Mean age of Case group areca nut users was 25.61±5.25 years, and mean age of control group non users was 26.62±5.17 years. In Case group areca nut users, Gutkha users were 64 (34.8%), pan users 47(25.5%), Supari users 43 (23.4%) and Mainpuri users 30 (16.3%). Systolic blood pressure was significantly increased in areca nuts and its products users as compare to control group. The systolic blood pressure was 126.34±11.14 mmHg in case group while in control group was found 118.67±12.49 mmHg with highly significant p-value 0.0001. Diastolic blood pressure is significantly increased in areca nuts and its products users as it was 84.7826±6.76 mmHg in case group as compare to control group 78.88±7.68 mmHg with highly significant p-value 0.0001. The frequency of hypertension was found more in case group areca nut and its products users as present in 28.80% of participants, as compare to 17.39% in control group. CONCLUSION: It is concluded that areca nuts and its products adversely affects blood pressure in such a way that it increases systolic blood pressure and diastolic blood pressure and hypertension was more prevalent in areca nut products users.